Cytokine Profiling in Low- and High-Density Small Extracellular Vesicles from Epidermoid Carcinoma Cells - Joseph P. Flemming; Brianna L. Hill; Lauren Anderson-Pullinger; Larry A. Harshyne; Mỹ G. Mahoney (Elsevier, 2021)
Exosomes or small extracellular vesicles (sEVs) are membrane-bound nanoparticles that carry various macromolecules and act as autocrine and paracrine signaling messengers. In this study, sEVs from epidermoid carcinoma cells influenced by membrane presentation of the glycoprotein desmoglein 2 and its palmitoylation state were investigated. In this study, sEVs were isolated by sequential ultracentrifugation followed by iodixanol density gradient separation. They were then subjected to multiplex profiling of cytokines associated with the surface of intact sEVs. The results revealed a previously undescribed active sorting of cytokines onto the surface of low-density and high-density sEV subpopulations. Specifically, an altered surface presentation of desmoglein 2 decreased FGF-2 and VEGF in low-density sEVs. In addition, in response to desmoglein 2, IL-8 and RANTES were increased in low-density sEVs but only slightly decreased in high-density sEVs. Finally, IL-6 and G-CSF were increased dramatically in high-density sEVs. This comprehensive analysis of the cytokine production profile by squamous cell carcinoma‒derived sEVs highlights their contribution to immune evasion, pro-oncogenic and proangiogenic activity, and the potential to identify diagnostic disease biomarkers.